2016
DOI: 10.1111/chd.12426
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral tissue oxygenation index and lactate at 24 hours postoperative predict survival and neurodevelopmental outcome after neonatal cardiac surgery

Abstract: Cerebral TOI combined with lactate at 24 hours postoperative are accurate non-invasive predictive biomarkers of patient survival and neurodevelopmental outcome in neonates with CHD undergoing cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 36 publications
1
62
1
2
Order By: Relevance
“…Cerebral NIRS has been proposed as an indicator of perfusion, and lower cerebral NIRS values have been associated with poorer outcomes in some pediatric surgeries. [27][28][29] Lumbar NIRS during kidney transplantation is a recently proposed use for this technology and appears to correlate with markers of graft function and perfusion. 30 Many patients come to the operating room with a dialysis cath- Another interesting finding of the current survey is the ongo- despite a delayed recovery of renal function after deceased donor kidney transplantation in children.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral NIRS has been proposed as an indicator of perfusion, and lower cerebral NIRS values have been associated with poorer outcomes in some pediatric surgeries. [27][28][29] Lumbar NIRS during kidney transplantation is a recently proposed use for this technology and appears to correlate with markers of graft function and perfusion. 30 Many patients come to the operating room with a dialysis cath- Another interesting finding of the current survey is the ongo- despite a delayed recovery of renal function after deceased donor kidney transplantation in children.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the interest in lactate in relation to the cerebral oxygenation in the neonatal period increased in the last years. Eighteen studies were identified, which investigated cerebral oxygenation and blood lactate level in neonates (7,11,13,15,16,18,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). However, only one of these publications demonstrated a negative association between cerebral oxygenation and lactate (7), and three studies found no association (11,23,29) between these factors.…”
Section: Lactate Level and Cerebral Oxygenationmentioning
confidence: 99%
“…Postoperative lactate levels and derived variables have been described as an early outcome predictor, particularly of survival but also for developmental outcome in children with CHD undergoing repair or palliation with cardiopulmonary bypass. 24,46,47…”
Section: Association Between S100b and Routine Monitoring Datamentioning
confidence: 99%